PENGARUH ASET, BELANJA DAERAH, TOTAL ASET DAN TOTAL BELANJA TERHADAP MATURITAS SPIP (SISTEM PENGENDALIAN INTERN PEMERINTAH) PEMERINTAH DAERAH JAWA BARAT - Daniel, Daniel; Chariri, Anis (Diponegoro Journal of Accounting, 2024)
This study aims to obtain empirical evidence and analyze the effect of assets, regional expenditure, total assets and total expenditure on the maturity of SPIP (government internal control system). Independent variables of assets, regional expenditure, total assets and total expenditure are projected in the financial statements assessed through the results of the West Java BPK audit 2021-2022, while the Government Internal Control System is projected in the West Java BPKP audit results 2021-2022 which are assessed through the SPIP Maturity Level.The population in this study is the West Java regional government which has been audited by BPK and BPKP in 2021 and 2022. There are 70 research samples used in accordance with predetermined criteria. The research data analysis used descriptive statistical analysis, classical assumption test and ordinal logistic regression analysis.Data analysis was performed using multiple linear regression. The results of this research analysis show that at the first point that Asset SPI has a significant influence on SPIP maturity in districts and cities in West Java Province with a contribution of the influence given of 31.2%, meaning that the greater the value of Asset SPI will have an impact on increasing the value of SPIP maturity, then at the second point Regional Expenditure SPI has a significant influence on SPIP maturity in districts and cities in West Java Province with a contribution of the influence given of 18%, meaning that the greater the value of SPI Regional Expenditure will have an impact on increasing the value of SPIP maturity, then at the third point total Regional Expenditure does not have a significant effect on SPIP maturity in districts and cities in West Java Province, meaning that changes in the value of total Regional Expenditure will not necessarily have an impact on changes in SPIP maturity value, and finally at point 4 Total Assets do not have a significant effect on SPIP maturity in districts and cities in West Java Province.